2004
DOI: 10.2139/ssrn.633082
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Run Relationship between House Prices and Rents

Abstract: I show that when house prices are high relative to rents (that is, when the rent-price ratio is low) changes in real rents tend to be larger than usual and changes in real prices tend to be smaller than usual. Standard error-correction models provide inconclusive results about the predictive power of the rent-price ratio at a quarterly frequency. I use a long-horizon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
162
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(184 citation statements)
references
References 19 publications
18
162
1
3
Order By: Relevance
“…Gallin (2008), Plazzi, Torous, and Valkanov (2010), and Engsted and Pedersen (2012) (see Ghysels, Plazzi, Torous, and Valkanov (2012) for a survey on forecasting real estate prices). Our study is also related to an extensive literature analyzing the role of expectations in house price determination, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Gallin (2008), Plazzi, Torous, and Valkanov (2010), and Engsted and Pedersen (2012) (see Ghysels, Plazzi, Torous, and Valkanov (2012) for a survey on forecasting real estate prices). Our study is also related to an extensive literature analyzing the role of expectations in house price determination, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated disparity between US house prices, population increases and building costs and suggested there is a strong element of speculation in the current housing market that is not justified by fundamentals. Gallin (2004) also used US data to explore the long run relationship between house prices and rents. Gallin concluded that house prices do correct back to rents rather than rents correcting to house prices.…”
Section: Introductionmentioning
confidence: 99%
“…Nor do we analyze whether the housing market was overvalued in 2005 and 2006, and whether a collapse of house prices was therefore, to some extent, predictable. There was a lively debate during that period, with some arguing that housing was reasonably valued (see Himmelberg, Mayer, andSinai 2005 andMcCarthy andPeach 2004) and others arguing that it was overvalued (see Gallin 2006, Gallin 2008, and Davis, Lehnert, and Martin 2008.…”
mentioning
confidence: 99%